Graded 2D/3D Perovskite Heterostructure for Efficient and Operationally Stable MA‐Free Perovskite Solar Cells - Yao, Qin; Xue, Qifan; Li, Zhenchao; Zhang, Kaicheng; Zhang, Teng; Li, Ning; Yang, Shihe; Brabec, Christoph J.; Yip, Hin‐Lap; Cao, Yong (Advanced materials (Weinheim), 2020)
Almost all highly efficient perovskite solar cells (PVSCs) with power conversion efficiencies (PCEs) of greater than 22% currently contain the thermally unstable methylammonium (MA) molecule. MA‐free perovskites are an intrinsically more stable optoelectronic material for use in solar cells but compromise the performance of PVSCs with relatively large energy loss. Here, the open‐circuit voltage (Voc) deficit is circumvented by the incorporation of β‐guanidinopropionic acid (β‐GUA) molecules into an MA‐free bulk perovskite, which facilitates the formation of quasi‐2D structure with face‐on orientation. The 2D/3D hybrid perovskites embed at the grain boundaries of the 3D bulk perovskites and are distributed through half the thickness of the film, which effectively passivates defects and minimizes energy loss of the PVSCs through reduced charge recombination rates and enhanced charge extraction efficiencies. A PCE of 22.2% (certified efficiency of 21.5%) is achieved and the operational stability of the MA‐free PVSCs is improved. The efficiency and operational stability of MA‐free FA0.95Cs0.05PbI3 perovskite solar cells can be simultaneously enhanced by the incorporation of the β‐guanidinopropionic acid (β‐GUA) molecule. The introduction of β‐GUA forms a 2D/3D hybrid perovskite phase, which effectively passivates the surface defects, resulting in an impressive power conversion efficiency of 22.2% with a substantial increase in Voc (from 1.01 to 1.14 V).